PENINGKATAN KETERAMPILAN ANAK PANTI ASUHAN MELALUI PELATIHAN MULTIMEDIA KREATIF - Februariyanti, Herny; Wibowo, Jati Sasongko; Wibisono, Setyawan (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2017)
Problems faced by the partners with regard to the continuation of life for orphans who have graduated from high school level, namely 1) Inability manager of an orphanage in financing the continuation of study to pursue the course for foster children; 2) Limitations orphanage in get- ting a job; (3) Lack of skill in the field of multimedia orphanage in capturing the job opportunities in the world of multimedia, especially digital printing industry. Currently the workforce with the skills of graphic design and multimedia has considerable opportunities in the industry engaged in creative multimedia. In Semarang and surrounding digital printing business continues to grow and evolve. The solution offered in this community service is a foster child skill enhancement through training with the stages in creative multimedia solutions: (1) Method IbM, namely creative multimedia training for orphans; (2) The activity plan and the involvement of partners in the implementation of a series of multimedia training activities; (3) Participation IbM partner with the team, partners active role in sup- porting the education and training of the design and production of creative multimedia merchandise.